2002
DOI: 10.1200/jco.2002.08.087
|View full text |Cite
|
Sign up to set email alerts
|

High Response Rate to Cisplatin/Etoposide Regimen in Childhood Low-Grade Glioma

Abstract: Cisplatin and etoposide combined treatment is one of the most active regimens for LGG in children and allows avoidance of radiotherapy in the vast majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
1
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(93 citation statements)
references
References 43 publications
2
87
1
3
Order By: Relevance
“…Children 5 years of age or younger had a notably more favorable rate of response. More recently, Massimino et al 52 reported a 78% PFS over 3 years with cisplatin and etoposide, with improved visual acuity in most patients and acceptable toxicity profiles. Temozolomide has also been shown to be useful in stabilizing disease in more than 50% of patients without significant toxicity 26 and is considered an option in patients with progressive OPG in whom first-line therapy has failed.…”
Section: Chemotherapy For Opgsmentioning
confidence: 99%
“…Children 5 years of age or younger had a notably more favorable rate of response. More recently, Massimino et al 52 reported a 78% PFS over 3 years with cisplatin and etoposide, with improved visual acuity in most patients and acceptable toxicity profiles. Temozolomide has also been shown to be useful in stabilizing disease in more than 50% of patients without significant toxicity 26 and is considered an option in patients with progressive OPG in whom first-line therapy has failed.…”
Section: Chemotherapy For Opgsmentioning
confidence: 99%
“…There is clear evidence both in vivo and in vitro of strong synergism between carboplatin and etoposide (Stein et al, 1999). A recent study showed the activity of a CBCDA (carboplatin) -VP-16 (etoposide)-based therapy in the treatment of low-grade gliomas in children (Massimino et al, 2002). The efficacy of CBCDA or cisplatin (CDDP) in combination with etoposide has been evaluated in various schedules in other trials in high-grade gliomas with various results (Buckner et al, 1990;Boiardi et al, 1991;Jeremic et al, 1992).…”
mentioning
confidence: 99%
“…Other traditional chemotherapy agents such as CDDP were somehow restricted by their limited ability to across the blood-brain barrier and could not reach the effective concentration in the tumor sites. CDDP alone or combined with other chemotherapy agents has been used to treat the lowgrade, newly diagnosed, or recurrent glioblastoma (45)(46)(47). The obstacle of CDDP being the first-line drug for glioma chemotherapy may only be hindered by its ability to reach the effective concentration at tumor site, because local chemotherapy of glioblastoma multiforme with CDDP followed by irradiation is proven to be well tolerated and effective (48).…”
Section: Discussionmentioning
confidence: 99%